(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
Translation plays a crucial role in bridging linguistic and cultural gaps between different languages and societies. It serves as a key process in the dissemination of knowledge, literature, technology, and culture across the globe. This article explores the significance of translation in the field of linguistics, examining its historical development, theoretical foundations, and its impact on language structure, meaning, and communication. It also highlights various translation approaches, such as formal equivalence and dynamic equivalence, and discusses the challenges faced by translators in conveying meaning accurately and effectively. Ultimately, translation serves as a bridge not only between languages but also between cultures, promoting cross-cultural understanding and facilitating global communication.